2022
DOI: 10.1038/s41523-022-00472-4
|View full text |Cite
|
Sign up to set email alerts
|

High GPER expression in triple-negative breast cancer is linked to pro-metastatic pathways and predicts poor patient outcomes

Abstract: Triple-negative breast cancer (TNBC) is a particularly aggressive and heterogeneous disease with few effective targeted therapies and precision therapeutic options over a long period. It is generally considered that TNBC is an estrogen-independent breast cancer, while a new estrogen receptor, namely G protein-coupled estrogen receptor (GPER), is demonstrated to mediate estrogenic actions in TNBC. Based on our transcriptomic analysis, expression of GPER was correlated with clinicopathological variables and surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…In vivo studies revealed that breast cancer in GPER-knockout mice resulted in diminished lung metastases compared with that in wild-type mice, indicating that animals with low or no GPER expression tend to develop less aggressive breast tumors ( Marjon et al, 2014 ). Recent research has shown a significant correlation between GPER abundance and high-risk TNBC, characterized by G3 tumors, distant metastasis, stage III, and lymph node metastasis ( Xu et al, 2022 ). Differing opinions suggest that GPER expression may suppress tumor initiation and progression ( Weißenborn et al, 2014 ).…”
Section: G Protein-coupled Estrogen Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies revealed that breast cancer in GPER-knockout mice resulted in diminished lung metastases compared with that in wild-type mice, indicating that animals with low or no GPER expression tend to develop less aggressive breast tumors ( Marjon et al, 2014 ). Recent research has shown a significant correlation between GPER abundance and high-risk TNBC, characterized by G3 tumors, distant metastasis, stage III, and lymph node metastasis ( Xu et al, 2022 ). Differing opinions suggest that GPER expression may suppress tumor initiation and progression ( Weißenborn et al, 2014 ).…”
Section: G Protein-coupled Estrogen Receptormentioning
confidence: 99%
“…Elevated GPER expression is directly related to a poor prognosis in TNBC ( Steiman et al, 2013 ; Xu et al, 2022 ). Specifically, decreasing GPER expression with siRNA has been demonstrated to effectively inhibit the proliferation of TNBC cells ( Girgert et al, 2012 ; 2014 ).…”
Section: Mechanism Of Gper In Tnbcmentioning
confidence: 99%
“…GPER, a seven transmembrane domain protein, that can trigger rapid cellular effects of estrogen [ 87 ], is also expressed in different organs such as liver and adipose tissue in addition to the mammary gland [ 88 ]. GPER expression has also been reported in several types of breast cancer cells [ 89 ]. Its stimulation by estrogen increases cAMP concentrations and the mobilization of intracellular calcium [ 90 , 91 ].…”
Section: Er-positive Breast Cancermentioning
confidence: 99%
“…However, Kyriakopoulou et al have reported that ERβ mediating EGFR induces aggressiveness and stemness of TNBC (Kyriakopoulou et al, 2020;Kyriakopoulou et al, 2022). G protein-coupled estrogen receptor 1 (GPER1), a member of G protein-coupled receptors (GPCRs), is activated by estradiol, and GPER1 expression is correlated with increasing aggressiveness of TNBC (Girgert et al, 2019;Xu et al, 2022). In a recent study, the anti-invasive effect of ERβ agonists was increased by GPER suppression (Schmitz et al, 2022); however, ERβ1 did not directly regulate the expression of GPER mRNA.…”
Section: Erβ1 Regulates the Activation Of Membrane Receptors And Down...mentioning
confidence: 99%